Semi-transparent central stop in high-resolution X-ray ptychography using Kirkpatrick-Baez focusing - Robin Niklas Wilke and Malte Vassholz and Tim Salditt (Acta crystallographica. Section A, Foundations and advances, 2013)
A ptychographic coherent X-ray diffractive imaging (PCDI) experiment has been carried out using 7.9 keV X-rays and Kirkpatrick–Baez focusing mirrors. By introducing a semi-transparent central stop in front of the detector the dynamic range on the detector is increased by about four orders of magnitude. The feasibility of this experimental scheme is demonstrated for PCDI applications with a resolution below 10 nm. The results are compared with reference data and an increase of resolution by a factor of two is obtained, while the deviation of the reconstructed phase map from the reference is below 1%.
Keywords: ptychography; Kirkpatrick–Baez mirrors; semi-transparent central stop; semi-transparent beam stop; coherent diffractive imaging; phase reconstruction